PCI Revascularization Strategies in Patients with Acute Myocardial Infarction and Multivessel Disease - Laksono, Sidhi; Widyani, Wella (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: The incidence of Acute Myocardial Infarction (AMI) accompanied by Multivessel Disease (MVD) has increased annually, necessitating appropriate revascularization strategies to minimize clinical risks. Objective: This study aimed to evaluate various revascularization strategies using Percutaneous Coronary Intervention (PCI) that can be applied in patients with AMI and MVD. Methods: A systematic review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The keywords used were (“Revascularization